Acute effect of caffeine consumption on isotonic muscular strength and endurance: A systematic review and meta-analysis - Polito, M. D.; Souza, D. B.; Casonatto, J.; Farinatti, P. (Science & Sports, 2016)
Objectives: The aim of the present study was to perform a systematic review and meta-analysis of the acute effects of caffeine ingestion on maximal strength and muscular endurance in isotonic resistance exercises. Equipment and methods: Up until March 2015, 17 studies which met the inclusion criteria, 42 trials related to muscular endurance and 5 trials related to muscular strength, were found from a search in the following databases: PubMed, ISI Web of Knowledge, SportDiscus, Scielo, Lilacs, Medcarib, Ibecs and ProQuest Dissertations & Theses. The effect sizes were calculated as the standardized mean difference and meta-analysis were completed using a random-effects model. Results: No significant effects were identified for gender, muscle location, muscle size, dosage of caffeine or form or timing of pre-exercise caffeine consumption on performance at maximum strength. For muscular endurance, all moderators were related to improve performance after caffeine intake (P < 0.01). The between groups analysis showed no differences with regard to the effect sizes in the comparisons for muscle location (P = 0.09); muscle size (P = 0.12); caffeine dosage (P = 0.08); and form of intake (P = 0.24). Effect size related to time of consumption pre-exercise was significant only for 60 min, with significant differences vs. 45 min and 90 min (P = 0.04). Comparisons between gender groups were not possible, since only one trial investigated females.